Management of Tomato Damping-off Disease in the Nursery Using of Trichoderma asperellum - Kishor Chand Kumhar; Kuldeep Kumar; Indu Arora; Arun Kumar Bhatia; Vinod Kumar Batra; Hans Raj (International Journal of Economic Plants)
The study was conducted during  2018−19 and 2019−20 to evaluate effectiveness of the Trichoderma asperellum liquid formulation for the management of tomato damping-off in the nursery. The experiment was conducted for two consecutive seasons in a randomized block design with seven treatments and three replications. T. asperellum formulation improved seed germination and controlled the damping-off diseases in tomatoes when compared with control. All the treatments performed better over control, in the first season, the antagonist’s application showed 75.75% seed germination; however, it was 60.13% in control. There was 10.93 to 20.38% seedling mortality due to disease which was comparatively lower than the control (26.98%). A similar trend of seed germination and disease incidence was observed in the second season. In addition to managing the disease, the antagonist certainly promoted vegetative growth which was reflected as increased shoot and root length in comparison to control during both seasons. During the first season, shoot length ranged 10.90–12.85 cm as compared to the control (8.72 cm) and root length ranged from 3.21–3.65 cm which was greater than the control. Almost a similar trend in the vegetative growth parameters of seedlings was observed during the second season. The present investigation showed that the tested antagonist’s formulation could efficiently manage the tomato damping-off as well as encouraged the vegetative growth of seedlings which ultimately ensured better and healthy seedling. This formulation can successfully be used through different methods to take care of tomato damping off.